Durability study of reinforced polyester composite used as pipe lining under artificial aging conditions. Issue 1 (1st January 2019) - Kharazmi, Parastou; Björk, Folke
Abstract: The aging of sewer infrastructure is an ongoing problem. As a result, different materials and methods are being used in alternative sewer rehabilitation approaches. This work was conducted to study one pipe lining, namely the reinforced polyester composite, under artificial aging; this was done to provide a better understanding of the material's performance under operating conditions, where it is regularly exposed to degrading factors such as heat and water. Aging of the material was monitored by means of several tests, including thermal and mechanical analyses, water absorption and microscopy. The results showed that the combination of aging in water and at high temperatures resulted in greater effects on the material compared to aging at high temperatures in dry conditions. Although the measured properties were affected significantly when immersed in water at high temperatures, the material showed acceptable properties at lower exposure temperatures close to the expected temperature inside sewer systems.